2019
DOI: 10.1002/slct.201900946
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Sterically Hindered and Unsymmetrical NpyNimOph Pincer‐Type Ligands and Their Palladium(II) Complexes: Catalytic Applications in Suzuki–Miyaura Reaction and Allylation of Aldehydes

Abstract: Palladium(II) complexes 1–4 [Pd(L1 to L4)Cl] derived from pincer‐type tridentate ligands having NpyNimOph donors were synthesized from ligands L1H to L4H (where L1H=(2‐phenyl‐2‐(pyridin‐2‐ylmethyl)hydrazono)methyl)phenol, L2H =[2‐((2‐phenyl‐2‐(pyridinyl‐2‐ylmethyl) hydrazono) methyl) phenol], L3H=[2‐((2‐benzyl‐2‐phenylhydrazono) methyl)‐4,6‐di‐tert‐butylphenol], and L4H=[2‐((2‐benzyl‐2‐phenylhydrazono)methyl)‐6‐(tert‐butyl)‐4‐methoxy phenol where H stands for dissociable proton)in quantitative yields. Synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Bourland et al reported a chiral tridentate ligand for vanadium metal salts; the catalysts were used in asymmetric selenide oxidation with in situ [2, 3] sigmatropic rearrangement . Although extensive research has been conducted on palladium complexes with [NNO]-, [ONO]-, and [CNO]-type tridentate ligands, there are only limited examples of palladium complexes possessing chiral tridentate ligands. , Therefore, we envisioned that the synthesis and application of such complexes would be a valuable research topic. Although extensive research has been conducted on palladium complexes with [NNO]-, [ONO]-, and [CNO]-type tridentate ligands, there are only limited examples of palladium complexes possessing chiral tridentate ligands More importantly, to the best of our knowledge, there is no report on palladium complexes possessing chiral [ONO]-type tridentate ligands …”
mentioning
confidence: 99%
“…Bourland et al reported a chiral tridentate ligand for vanadium metal salts; the catalysts were used in asymmetric selenide oxidation with in situ [2, 3] sigmatropic rearrangement . Although extensive research has been conducted on palladium complexes with [NNO]-, [ONO]-, and [CNO]-type tridentate ligands, there are only limited examples of palladium complexes possessing chiral tridentate ligands. , Therefore, we envisioned that the synthesis and application of such complexes would be a valuable research topic. Although extensive research has been conducted on palladium complexes with [NNO]-, [ONO]-, and [CNO]-type tridentate ligands, there are only limited examples of palladium complexes possessing chiral tridentate ligands More importantly, to the best of our knowledge, there is no report on palladium complexes possessing chiral [ONO]-type tridentate ligands …”
mentioning
confidence: 99%